2001
DOI: 10.1046/j.1365-2648.2001.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attendance at birth and maternal mortality rates: an exploration of United Nations’ data sets including the ratios of physicians and nurses to population, GNP per capita and female literacy

Abstract: As in the previous papers, caution is required regarding the validity and reliability of the UN data sources used in these analyses. Maternal mortality rates are particularly susceptible to inaccuracies. Nevertheless, the strength of the positive correlations suggests that real relationships are identified between the independent variables and the dependent variable of MMR. The strength of the linear and multiple correlations between births attended by trained personnel and lower MMRs indicates that maternal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 8 publications
5
71
1
Order By: Relevance
“…All health facilities in Caazapa Region were equipped with the essential minimum equipment to carry out primary healthcare services [31]. Robinson and Wharrad mentioned that deliveries attended by trained healthcare personnel in an appropriate and sanitary environment with essential, basic equipment reduced maternal mortality [32]. When essential equipment is available, an appropriate educational program promotes maternal health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…All health facilities in Caazapa Region were equipped with the essential minimum equipment to carry out primary healthcare services [31]. Robinson and Wharrad mentioned that deliveries attended by trained healthcare personnel in an appropriate and sanitary environment with essential, basic equipment reduced maternal mortality [32]. When essential equipment is available, an appropriate educational program promotes maternal health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using global data found no significant association between doctor density and infant mortality (Kim and Moody 1992), and no association between doctor density and either infant or maternal mortality (Hertz, Hebert, and Landon 1994). Three studies found no association between nurse density and maternal mortality, infant or under-five mortality, and infant mortality (Kim and Moody 1992;Robinson and Wharrad 2000;Robinson and Wharrad 2001). No association was found between the concentration of doctors and nurses and the utilization of 6 'essential' health services in low and middle income countries, leading to speculation that other health workers, who had not been included in the research, were undertaking aspects of service provision (Kruk et al 2009), a point to which we return.…”
Section: Relationship Between Healthcare Worker Density and Populatiomentioning
confidence: 99%
“…More recent quantitative analyses of the association between the density of healthcare professionals and mortality rates have given contradictory results. Using global data, a higher density of doctors has been shown to have a positive effect on maternal, infant, and under-five mortality (Robinson and Wharrad 2001) and a higher density of doctors, nurses and midwives was positively associated with maternal mortality rate and to a lesser extent with infant mortality rate and under-five mortality (Anand and Bärnighausen 2004). In 'developed' countries doctor density has been found to have a negative effect on infant and perinatal mortality and no effect on maternal mortality (Cochrane, St Leger, and Moore 1978).…”
Section: Relationship Between Healthcare Worker Density and Populatiomentioning
confidence: 99%
“…4 Increasing evidence is beginning to emerge that maternal and infant survival is proportionately correlated to the number of health workers providing obstetric care that includes anaesthesia. 5,6 The delivery of surgical (including obstetrics and trauma) care is highly dependent on the availability and retention of a trained anaesthesia health workforce. The United Kingdom Confidential Enquiry for Perioperative Death in 1987 reported one death per 185 000 anaesthetic procedures; whereas in Zambia (University teaching hospital), it was one death per 1925.…”
Section: Importance Of Anaesthesia Workforcementioning
confidence: 99%